Ethiopia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1994)
This paper describes economic developments in Ethiopia during 1990-94. In 1992/93, there was a significant recovery in the economy, which was reflected in virtually all sectors, with real GDP rebounding by an exceptional 12.3 percent. Although the improved security situation in the country and, subsequently, the emergence of a favorable economic and political climate set the stage for the recovery, a number of additional factors contributed to this outcome. In the agricultural sector, good weather conditions, coupled with increases in land under cultivation and greater fertilizer usage, led to a bumper crop.